2010
DOI: 10.1097/cji.0b013e3181d32f01
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory (FoxP3+) T-cell Tumor Infiltration Is a Favorable Prognostic Factor in Advanced Colon Cancer Patients Undergoing Chemo or Chemoimmunotherapy

Abstract: Antitumor immune response and chemotherapy-induced immunomodulation in colon cancer patients represented the rationale to design new strategies, like GOLFIG chemoimmunotherapy (gemcitabine, oxaliplatin, 5-fluorouracil/folinic acid, granulocyte macrophage colony-stimulating factor, and aldesleukine), that resulted a safe and very active regimen. Antitumor activity and immunity feedback to GOLFIG were strictly correlated with the best outcome observed in patients with autoimmunity signs, increase of central memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
144
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(156 citation statements)
references
References 31 publications
8
144
3
1
Order By: Relevance
“…This situation reflects the steadystate or homeostatic conditions within a given tumor tissue or tumor microenvironment. The clinical correlates for our in vitro findings are those patients and clinical studies of solid as well as non-solid tumors in which investigators found tumor-infiltrating Treg cells to be a good prognostic factor [29][30][31][32]. Examples include lymphomas as Hodgkin lymphoma where investigators found a positive correlation between high Treg cell infiltration and higher rates of survival [32].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This situation reflects the steadystate or homeostatic conditions within a given tumor tissue or tumor microenvironment. The clinical correlates for our in vitro findings are those patients and clinical studies of solid as well as non-solid tumors in which investigators found tumor-infiltrating Treg cells to be a good prognostic factor [29][30][31][32]. Examples include lymphomas as Hodgkin lymphoma where investigators found a positive correlation between high Treg cell infiltration and higher rates of survival [32].…”
Section: Discussionmentioning
confidence: 85%
“…1 Treg cells in colorectal cancer [30,33]. Further, Badoual et al reported that Treg cells are positively correlated with locoregional control in patients with head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 However, the role of Tregs in human CRC patients is still controversial. [12][13][14][15][16] Given the inconsistent results concerning the prognostic value of Tregs in patients with CRC, it is not surprising that there is to date no clinical trial reporting effective immunotherapies targeting Tregs in CRC. Therefore, it is drastically needed to understand the exact role of those regulatory T cells in human CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor infiltration by different inflammatory cells has been correlated with prognosis and tumor progression in different tumors including EOC [95][96][97][98]. Among these cells, tumor associated macrophages (TAMs) have recently demonstrated to exert a significant immune suppressive effect together with a pro-angiogenic activity (M2 polarization) [99].…”
Section: Parp Inhibitorsmentioning
confidence: 99%